Increasing diagnoses per patient admission at a specialist children’s hospital: A retrospective study - Stuart A. Bowyer; John Booth; Daniel Key; Eleni Pissaridou; William A. Bryant; Harry Hemingway; Neil J. Sebire (PLoS ONE, 2025)
Objective In adult practice there is recognition that average patient complexity is increasing, with a greater proportion of patients having multiple diagnoses or comorbidities. This study aims to examine whether there has been a change in number of recorded coexisting diagnoses per patient over a 24-year period for children attending as in-patients to a specialist children’s hospital in England. Methods Following all in-patient admissions, patient episodes are allocated specific diagnosis codes (ICD-10) by a specialist clinical coding team according to standard NHS criteria and guidance. We examine the number of coexisting diagnoses allocated per patient admission over a 24-year period. Results From a total of 278,579 overnight in-patient admissions during the study period (2000–2023) there were 1,023,276 ICD-10 patient diagnoses. The mean number of diagnoses per admission increased from 2.72 to 10.43 over the period (Kendall’s tau statistic of 0.93; p-value < 0.001), an increase of 284% (95% confidence interval 275% - 293%). Conclusions Over recent decades, the recorded complexity of patients attending a specialist children’s hospital appear to have increased significantly, with an almost 3-fold increase in the number of coexisting diagnoses present per admission. The cause of this finding cannot be determined from the data; however, it appears to be gradual and consistent, and across all speciality areas suggesting biological or referral factors rather than artefactual coding issues. Recognition of such a trend is important when interpreting retrospective data for AI, research, and planning purposes.